Prevalence of substance use disorder and psychiatric comorbidity burden among pregnant women with opioid use disorder in a large administrative database, 2009-2014 - Yun Shen; Wei-Hs; Richard Segal; Amie J. Goodin (Taylor & Francis Group, 2021)
Objectives Using data from the Healthcare Cost and Utilization Project (HCUP), we estimated prevalence of individual substance use disorders (SUDs) and psychiatric comorbidities among pregnant women with opioid use disorder (OUD) in the New York State from 2009 to 2014. Methods In this cross-sectional study, pregnancy outcome and gestational age at delivery were estimated, and OUD diagnosis during pregnancy or at delivery discharge was identified. Prevalence of SUDs and psychiatric comorbidities were then calculated. Results Among 1,463,302 pregnant women, 8324 (0.57%) were diagnosed with OUD during pregnancy or at delivery. The most frequent SUDs or psychiatric comorbidities among pregnant women with OUD were non-opioid SUD (78.2%), followed by tobacco use disorder (74.9%), generalized anxiety disorder (38.0%), major depressive disorder (36.9%), cannabis use disorder (28.3%) and cocaine use disorder (27.4%). Conclusions Most pregnant women with OUD were diagnosed with at least one non-opioid SUD and tobacco use disorder. Generalized anxiety disorder and major depressive disorder were also common, suggesting that mental health screenings should be prioritized for pregnant women with OUD.